Metrologi Legal sebagai Strategi Membangun Kepercayaan Konsumen untuk Mendorong Inovasi Layanan pada Toko Emas - Urian Firmansyah AR; Zulkieflimansyah Zulkieflimansyah; Muhamad Hidayat (LPPM Institut Pendidikan Nusantara Global, 2026)
Legal metrology has traditionally been viewed as a regulatory instrument for ensuring measurement accuracy and consumer protection. However, its strategic role as a mechanism for building consumer trust and fostering service innovation has received limited scholarly attention, particularly in the gold retail sector. This study examines the relationships among Legal Metrology, Consumer Trust, and Service Innovation, while investigating the mediating role of Consumer Trust in the relationship between Legal Metrology and Service Innovation on gold stores in Sumbawa Regency. A quantitative explanatory research design was employed involving 146 respondents selected through purposive sampling, whereas data collection was operationally conducted using accidental sampling among eligible consumers. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that Legal Metrology has positive and statistically significant relationships with Consumer Trust (β = 0.828; p < 0.001) and Service Innovation (β = 0.351; p = 0.017). Consumer Trust also demonstrates a positive and statistically significant relationship with Service Innovation (β = 0.442; p = 0.005) and partially mediates the relationship between Legal Metrology and Service Innovation (β = 0.366; p = 0.009). These findings suggest that Legal Metrology should not only be viewed as a regulatory compliance mechanism but also as a managerial strategy for strengthening consumer trust and encouraging service innovation. This study contributes empirically by extending the application of Signaling Theory and Commitment–Trust Theory within the context of measurement-based gold retailing.